2022
DOI: 10.3390/v14050925
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Avian Influenza H5N6 Virus-like Particles as a Broad-Spectrum Vaccine Candidate against H5Nx Viruses

Abstract: Highly pathogenic avian influenza (HPAI) clade 2.3.4.4 viruses have been reported to be the source of infections in several outbreaks in the past decades. In a previous study, we screened out a broad-spectrum virus strain, H5N6-Sichuan subtype, by using a lentiviral pseudovirus system. In this project, we aimed to investigate the potential of H5N6 virus-like particles (VLPs) serving as a broad-spectrum vaccine candidate against H5Nx viruses. We cloned the full-length M1 gene and H5, N6 genes derived from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…To enhance the expression efficacy of the DNA vaccine gene, the AIV antigen gene isolated from the chicken was optimized and cloned into the pCAGGS vector, which is widely known to be highly expressed in eukaryotic cells because of its sequence containing the chicken β-actin promoter and CMV enhancer ( Jiang et al, 2007 ; Zhao et al, 2020 ).Using the optimized genes, we constructed 4 pCAGGS-optiDNAs expressing multiple HA or NA protein-coding genes, and found that the group containing 3 AIV fragments (pβH9N1SH5, pβH5N1SH9) had the fastest conversion rate and produced more significant HI, confirming that compared to the other vector combinations we investigated (monovalent or bivalent vaccines), trivalent antigenic vaccines were more able to induce H9N2 AIV HI antibodies. Subsequently, the virus-like particles ( VLPs ) formed by pβH9N1SH5 showed particle diameters of approximately 100 to 200 nm, which are consistent with the diameters of influenza viruses and influenza VLPs produced in different expression systems, such as mammalian cell expression systems and baculovirus-insect cell systems ( Wu et al, 2017 ; Yang et al, 2022 ). These results suggest that the pβH9N1SH5 plasmid expression efficiently assembles and releases VLPs, which in turn induce AIV HI antibodies.…”
Section: Discussionsupporting
confidence: 63%
“…To enhance the expression efficacy of the DNA vaccine gene, the AIV antigen gene isolated from the chicken was optimized and cloned into the pCAGGS vector, which is widely known to be highly expressed in eukaryotic cells because of its sequence containing the chicken β-actin promoter and CMV enhancer ( Jiang et al, 2007 ; Zhao et al, 2020 ).Using the optimized genes, we constructed 4 pCAGGS-optiDNAs expressing multiple HA or NA protein-coding genes, and found that the group containing 3 AIV fragments (pβH9N1SH5, pβH5N1SH9) had the fastest conversion rate and produced more significant HI, confirming that compared to the other vector combinations we investigated (monovalent or bivalent vaccines), trivalent antigenic vaccines were more able to induce H9N2 AIV HI antibodies. Subsequently, the virus-like particles ( VLPs ) formed by pβH9N1SH5 showed particle diameters of approximately 100 to 200 nm, which are consistent with the diameters of influenza viruses and influenza VLPs produced in different expression systems, such as mammalian cell expression systems and baculovirus-insect cell systems ( Wu et al, 2017 ; Yang et al, 2022 ). These results suggest that the pβH9N1SH5 plasmid expression efficiently assembles and releases VLPs, which in turn induce AIV HI antibodies.…”
Section: Discussionsupporting
confidence: 63%
“…One milligram protein of rg-viruses was used to immunize BALB/c mice with the addition of Freund’s complete adjuvant (CFA, Sigma, St. Louis, MO, USA) for priming and Freund’s incomplete adjuvant (IFA, Sigma, St. Louis, MO, USA). At the end of the immunization period, mice were sacrificed and the cardiac chambers serum sample were collected [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The neutralizing potential of these sera was tested against pseudoviruses expressing H5 and a wide array of NA antigens. In almost all cases, irrespective of H5N2, H5N6, or H5N8 subtypes, neutralizing activity was greater in the sera acquired from the H5N6 VLP-immunized mice [ 29 ]. Insect cell-derived VLPs expressing the HA antigens of multiple clades were demonstrated to be more efficacious than single antigens.…”
Section: Influenza Virusmentioning
confidence: 99%